Some hydrozoans (Cnidaria) from King George Island, Antarctica - Galea, Horia R.; Schories, Dirk (Zootaxa, 2012)
Twenty one species of shallow-water, benthic hydrozoans, belonging to nine families and fourteen genera, were found ina collection gathered from King George Island, South Shetland islands, during 2010 and 2011. Hydractinia angusta Hart-laub, 1904, Staurocladia charcoti (Bedot, 1908), Candelabrum penola (Manton, 1940), Orthopyxis norvegiae (Broch,1948), and Silicularia pedunculata (Jäderholm, 1904) are redescribed. Additional notes are provided on Schizotricha tur-queti Billard, 1906. Sertularella gaudichaudi (Lamouroux, 1824) is recognized as one of the most widely-distributed member of its genus in Antarctic waters. Taxonomic notes and updated synonymy are provided for some species.